Real-world outcomes of immunotherapy-based neoadjuvant therapy in resectable non-small cell lung cancer - Shen, Jie; Gu, Linping; Qi, Yuwen; Yao, Yaxian; Lu, Shun; Chen, Zhiwei (Frontiers in Immunology, 2023)
Objectives Recent clinical studies have demonstrated that immunotherapy-based neoadjuvant therapy have promising effectiveness for patients with resectable non-small cell lung cancer (NSCLC) in terms of pathologic response. Therefore, we performed this study to investigate whether immunotherapy-based neoadjuvant therapy is effective and safe for patients with resectable NSCLC.This open-label observational two-arm clinical study was performed at Shanghai Chest Hospital in China with patients who had resectable NSCLC and received two to three cycles of immunotherapy-based neoadjuvant therapy or neoadjuvant chemotherapy alone, followed by surgical resection. The primary endpoint was a major pathologic response (MPR). The secondary endpoints include a complete pathological response (pCR), a radiologic response to neoadjuvant therapy (TRR), event-free survival (EFS), and overall survival (OS).Results A total of 51 patients was included in this clinical study, of which 31 patients received immunotherapy-based neoadjuvant therapy and 20 patients received neoadjuvant chemotherapy alone.The percentage of patients achieving a major pathologic response was 41.9% with immunotherapy-based neoadjuvant therapy and 15.0% (95% CI, 0.008 to 0.468; P = 0.043) with neoadjuvant chemotherapy alone. The percentage of patients with pathologic complete response was 19.4% in the immunotherapy-based group and 5% (95% CI, -0.069 to 0.318; P = 0.223) in the chemotherapy group. The radiographic response rate was 71% after immunotherapy-based neoadjuvant therapy and 60% (95% CI, -0.143 to 0.359; P = 0.417) after neoadjuvant chemotherapy. At a median follow-up of 28 months, the median EFS and OS endpoints were not reached.Conclusions Neoadjuvant immunotherapy offers a considerable advantage over chemotherapy alone for resectable NSCLC in terms of the major pathologic response. Moreover, it did not enhance the risk of adverse events or hinder surgical resection.